Information engineering of a software engineering ontology - Wongthongtham, Pornpit; Chang, Elizabeth; Dillon, Tharam S. (IEEE, 2005)
In this paper, we describe the preliminary result of the development and implementation of a Java-based system for information gathering, knowledge extraction and maintenance of software engineering ontology. The system is capable of manipulative ontology instances from the information repositories and information sources. Design of Software Engineering Ontology through the use of the body of software engineering knowledge together with Prof Ian Sommerville's book, as well as project management experiences, has not been a difficult task. However, the maintenance of the software development ontology and security of the Ontology are issues.